Keberlangsungan Pendidikan Agama Anak Petani Garam: Analisis Tingkat Ketahanan Keluarga pada Petani Garam di Kabupaten Pamekasan Madura - Choiri, Muttaqin; Qomaro, Galuh Widitya (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
Education is one of the instruments in realizing family resilience in supporting national development. For the Madurese community in general, religious education has very strong roots. This research was conducted in order to identify the level of family resilience through religious education, which functions as a measurable and structured aspect of family welfare for salt farmers. This qualitative research uses interviews, observation and documentation as data collection instruments. The results showed that the level of family resilience from the economic, social and cultural side shows the Resistance index for the whole family, on the other hand, for single families it shows the index of less resistance, this also has an impact on the sustainability of Islamic religious education for children in salt farmer families; namely family expectations, availability of sources and internalization of religious values in the life of whole families and single families. For nuclear families, the fulfillment of the variable of family resilience development has a role in supporting the continuity of religious education for children, such as the facilities and attention that leads to the emergence of children’s habits within the scope of salt farming families.